Ultraviolet Vision May Enhance the Ability of Reindeer to Discriminate Plants in Snow - Tyler, NJC; Jeffery, G; Hogg, CR; Stokkan, K-A (2014)
In reindeer/caribou (Rangifer tarandus), the lens and cornea of the eye transmit ultraviolet (UV) light, and the retinae respond to it electro-physiologically. Here we tie this finding to the unusual visual environment experienced by these animals and propose that their sensitivity to UV light enhances vision at the low luminance characteristic of the polar winter. For such visual enhancement to occur, it is essential that functional components of the environment, such as forage plants, be visually salient under natural UV luminance. However, it is not self-evident that this is the case. Although organic material generally absorbs UV radiation, powerful scattering of UV light by snow crystals may reduce the contrast with the background. We therefore recorded UV images of vegetation in situ on snow-covered pasture under natural winter (March) luminance in northern Norway. For each vegetation scene, we made three monochrome digital images, at 350 – 390 nm (UV-Only), 400 – 750 nm (No-UV), and 350 – 750 nm (control), respectively. Plants at the snow surface appeared in high achromatic contrast against snow in UV-Only images. The contrast was substantially greater in the UV-Only images than in corresponding images in which UV was blocked. We conclude that plants are visually salient under natural UV luminance at wavelengths to which Rangifer are sensitive. This sensitivity is likely to improve the animals’ ability to discriminate forage in snow, particularly at low but relatively UV-enriched twilight luminance.